ByzRev 07.2025.038: Rafał Quirini-Popławski, The Art of the Genoese Colonies of the Black Sea Basin (1261–1475): (The Medieval Mediterranean 136). Leiden – Boston: Brill 2023. - Olympios, Michalis (The Byzantine Review, 2025)
Rafał Quirini-Popławski, The Art of the Genoese Colonies of the Black Sea Basin (1261–1475) (The Medieval Mediterranean 136). Leiden – Boston: Brill 2023. 410 pp., 299 figures. – ISBN 978-90-04-53893-1 (paperback), 978-90-04-67890-3 (e-book)